The Sterile Corneal Post-Operative Melting Point - NSAID Induced Keratolysis After Cataract Surgery - Prasanna Venkatesh Ramesh; Shruthy Vaishali Ramesh; Meena Kumari Ramesh; Ramesh Rajasekaran (Delhi Journal of Ophthalmology)
Progressive sterile keratolysis is a rare yet potentially blinding condition after cataract surgery. Acute sterile corneal melt after cataract surgery is defined as: 1) occurrence of keratolysis within a month after cataract surgery, 2) absence of infection signs, and 3) appearance around paracentral cornea. Delayed detection in this 72 year old male with poor follo w up after cataract surgery resulted in near total corneal melt. The presumable factor responsible here could be long-term usage of NSAID (Nepafenac 0.1% eye drops). Screening for both ocular (Sjogren's syndrome) and systemic risk factors (rheumatoid arthritis) is essential to prevent such condition.